2021
DOI: 10.1021/jacs.1c09087
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of Li2MnO3 Electrodes in an All-Solid-State Thin-Film Battery Analyzed by Operando Hard X-ray Photoelectron Spectroscopy

Abstract: is a promising cathode candidate for Li-ion batteries because of its high discharge capacity; however, its reaction mechanism during cycling has not been sufficiently explicated. Observations of Mn and O binding energy shifts in operando hard X-ray photoelectron spectroscopy measurements enabled us to determine the charge-compensation mechanism of Li 2 MnO 3 . The O 1s peak splits at an early stage during the first charge, and the concentration of lower-valence O changes reversibly with cycling, indicating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 69 publications
1
28
0
3
Order By: Relevance
“…Some studies have demonstrated very challenging operando XPS measurements. 197–199 Of course, ASSBs have the advantage to resist ultra-high vacuum, even though it was discussed previously that sulphide-based solid electrolytes might need to be cooled down to avoid sulphur sublimation. Still, the fabrication of cells that can be cycled inside the analysis chamber of the XPS instrument remains a challenge as it can be difficult already not under operando conditions.…”
Section: In Situ and Operando Xps Measurementsmentioning
confidence: 99%
“…Some studies have demonstrated very challenging operando XPS measurements. 197–199 Of course, ASSBs have the advantage to resist ultra-high vacuum, even though it was discussed previously that sulphide-based solid electrolytes might need to be cooled down to avoid sulphur sublimation. Still, the fabrication of cells that can be cycled inside the analysis chamber of the XPS instrument remains a challenge as it can be difficult already not under operando conditions.…”
Section: In Situ and Operando Xps Measurementsmentioning
confidence: 99%
“…The model all-solid-state battery designed in this study comprised a 10-nm Al current collector, 35.2-nm Li 2 MnO 3 cathode, 180-μm Li 1+ x + y Al x (Ti,Ge) 2− x Si y P 3− y O 12 (LASGTP) solid electrolyte, 500-nm Li 3 PO 4 buffer layer, and 1-μm Li anode 21 . The positions of the bands of the five components with respect to the vacuum level are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This information has never been considered in battery development and serves as the starting point of this study. HAXPES and other methods were employed to elucidate the electrode reactions and properties, e.g., the crystal structure, formation and conversion of various redox species, and changes in the valences of the constituent elements during the charge–discharge reaction; these results, obtained via conventional investigations, have been described elsewhere 21 , 29 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All-inorganic solid-state batteries (AISSBs) attract great research interest due to the benefits in safety and energy density. , The thin-film battery, based on vacuum technology, is a type of AISSB that could reduce the thickness of solid-state electrolyte to a few microns and provide void-free electrode–electrolyte contact. A mini-version of thin-film battery, referred to as a microbattery, is already utilized in chips, sensors, and other tiny devices. The key step of fabricating a thin-film battery is the deposition technique.…”
Section: Introductionmentioning
confidence: 99%